Application and Prospect of CRISPR/Cas9 Technology in Reversing Drug Resistance of Non-Small Cell Lung Cancer - Huang, Lu; Liao, Zhi; Liu, Zhixi; Chen, Yan; Huang, Tingwenli; Xiao, Hongtao (Frontiers in Pharmacology, 2022)
Cancer drug resistance has always been a major factor affecting the treatment of non-small cell lung cancer, which reduces the quality of life of patients. The clustered regularly interspaced short palindromic repeats/CRISPR associated protein 9 (CRISPR/Cas9) technology, as an efficient and convenient new gene-editing technology, has provided multifaceted assistance to the clinic and accelerated the research of cancer and drug resistance. In this review, we introduce the mechanisms of drug resistance in non-small cell lung cancer (NSCLC), discuss how the CRISPR/Cas9 system can reverse multidrug resistance in NSCLC, and focus on drug resistance gene mutations. To improve the prognosis of NSCLC patients and further improve the quality of life of patients, it is necessary to utilize the CRISPR/Cas9 system in systematic research on cancer drug resistance.